تقييم فعالية طريقة مسح المقاطع العرضية للسفينة في تحديد ذراع عزم الاستعدال للسفن - بربهان, ميشيل; محمد, نسرين (Latakia University Journal -Engineering Sciences Series, 2017)
لتحديد منحني الاتزان العرضي المتعلق بالشكل يتم عادة تحديد خط الماء المتساوي الحجم لكل حالة تحميل، الأمر الذي يتطلب إعادة حسابات رياضية معقدة وطويلة مع اختلاف قيمة الغاطس الموافقة لكل حالة تحميلالهدف من هذا البحث هو بناء نموذج رياضي يسمح بتحديد منحني الاتزان العرضي المتعلق بالشكل عند جميع حالات التحميل المعتبرة للسفينة اعتماداً على قراءة المقاطع العرضية لبدن السفينة المحددة بالخطوط القطاعية العرضية المشكلة للمسقط الأمامي لرسمه الخطوط النظرية للسفينة. لا تحتاج هذه الطريقة إلى فرضيات مسبقة لإجراء الحسابات وهذا قد يسبب منطقياً رفع دقة الحسابات خلافاً للطرق الأخرى المستخدمة حاليا في تقييم الاتزان العرضي للسفن.أثبتت فعالية هذه الطريقة في اختصار الوقت والحصول على نتائج جيدة عن طريق مقارنتها مع النتائج التحليلية الخاصة بالسفينة الصندوقية، والسفينة ذات المقطع المثلثي و طريقة Pozdiunin التقريبية المعتمدة عالمياً، وتم أيضاً مقارنة نتائج هذه الطريقة مع قيم منحنيات الاتزان الثابتة الخاصة بوثائق سفينة تجارية حقيقية. إنّ نتائج تقييم ومعايرة الطريقة المدروسة تسمح باستخدامها في معايرة اتزان السفن، والاستخدام في إعمال بحثية لاحقة. In order to calculate the cross curve of stability related to ship form the water line of equal volume corresponding to each load draught should be determined. Therefore complex and long steps of mathematical calculations should be done for each vessel displacement. The goal of this research is to build a mathematical model enables the determination of cross curve of stability related to ship form for all ship displacements. This model is based on reading of the transverse sections of the ship projected on to a vertical transverse plane of the body plan. This method does not need to previous assumptions to perform calculations therefore the calculations accuracy could be increased in comparison with other methods currently in use to evaluate the transvers stability for ships. The efficiency of this method has been proven in saving time as well as in giving good results by comparing it with the analytical results for ships of box and trigonometric forms. The comparison includes Pozduinin approximate method which is largely used in ship world as well as the stability curves for real commercial ship. The good results of evaluation of cross curves of stability by the proposed method (scanning sections method) allow to generalize its use for validation of ship stability and other works research.